(3QSGdI aj aVjdI GdYdhe hGdUfGYGJs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3aUd bGd CHh fUQ eMeO Hf eMeO GdaGQGHi JZeOg Gddg aVdI GdYdhe hGdUfGYGJ EfeG jchf HEMOi KdGKI EeG HTQa GdehVhY hEeG HESJbUGA GdHQGgjf hEeG HYXe GdLOhi GdPjf ajg s
(3BNQgG (B:s
(3hYed HeG bjd Ef cd ebHhd eMPhQ efg gPG BNQ eG hLO ef GdJPGcjQ HNW CHj fUQ CHbgG dfaSi hcJHJgG dc dJJCedgG hGddg Gdehab Je GdcJGH HYhf GdMb s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeQJH GdGLOi (B/ (3GdBUajI HMjOQ CHGO (B((3eLGejY (B13(8)) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs